Role of Financial and Non-financial Incentives on Employee’s Performance: A Study on the Banking and Insurance Sectors of Nepal - Acharya, Anjana; Oli, Sudan Kumar (Journal of Innovation in Academia, 2024)
As the banking and insurance are service sector industries, the competence and dedication of the employees of these sectors significantly influence customer satisfaction and organizational success. Therefore, the performance of employees stands as a crucial factor determining the success of banks and insurance companies. This research aims to explore the impact of financial and non-financial incentives on the performance of employees working in the Nepalese banking and insurance sectors. A structured questionnaire was employed to collect the data for the study from 400 sample employees of these sectors by using a non-probability sampling method. For the analysis of data, tools such as Cronbach’s Alpha analysis and Regression analysis was carried out to assess the relationship among the variables. In addition, to analyze the findings of ordinal variables, Ordinal Logistic Regression Model was used. The study found a positive correlation between financial incentives (bonuses and fringe benefits) and employee performance. By the value of Ordinal Logistic Regression, factors like age, experience, and job security did not indicate a significant impact on employee performance. In contrast to that, factors like age, experience, and job security did not indicate a significant impact on employee’s performance. The findings of the study also challenge the theoretical assumption that higher pay directly leads to improved performance, suggesting that high pay expectations might lead to performance pressure and reduced employee performance. Similarly, while working conditions were not significant, emphasizing upgrades solely based on this factor may not be justified in the banking and insurance sectors based on this research. Recommendations include the necessity for managers or HR professionals to strike a balance between financial and non-financial incentives to optimize employee performance and thereby enhance company productivity.